PENGARUH LITERASI TERHADAP HAFALAN AL-QUR’AN SISWA DI SDN 07 SIGIRAN - Vira Rahmadianti; Fenny Ayu Monia (Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this study was to determine the effect of literacy on students’ Al Qur’an memorization. The research method used by researchers is field research, by directly observing the events that occurred at SDN 07 Sigiran. In this modern era, many students’ are influenced by technological developments. Technological developments can bring both positive and negative influenced. One of the negative effects of technological developments ia the lack of interest and desire of students’ to memorize the Al-Qur’an. Therefore, the school as an educational institution for students strives to increase students’ interest and desire to memorize the Al-Qur’an. One effert that schools can do is to read the koran regularly every morning before the teaching and learning process takes place. Keywords: Literacy, Memorization, Students